Life cycle costing of industrialized building system and conventional building system - Al-Attabi, Ali Mohammed Ali Naji (2014)
Life cycle costing (LCC) is the process of identifying and documenting the initial cost and future cost of the project throughout the lifetime of the building. It is important in determining the design alternatives through analyzing the total cost of ownership over the life span of an asset. Lack of adaptation of the residents with the house design leads them to adjust the house to fit their needs. The aim of this study is to calculate the life cycle costing of the new project as well as the changes and modifications throughout assumed lifespan of two generations for conventional and industrialized building system houses. Furthermore, it also introduces an alternative design to suit the householder needs. To achieve the aims, a research questionnaire survey was distributed among householders to obtain the money spent on housing and the modifications that occurred in the house throughout their home occupation. Moreover, the Net Present Value (NPV) method was adopted to achieve the IBS life cycle costing. Besides, Auto CAD software use to draw different house layouts to fit the residents’ requirements obtained from the questionnaire. However, the results showed that the modifications cost of a conventional house equal to 57% of house selling price and the LCC of the conventional building system equal to 67% of the IBS. The research shows that the IBS is a better method of construction as an alternative to a conventional building system.